**radical**a^2-z^2/

**radical**a^2+z^2 Note: Both the denominator and numerator are under radical

Differentiate

H(z)=ln **radical** a^2-z^2/**radical** a^2+z^2 Note: Both the denominator and numerator are under radical

Differentiate y=x^lnx

Thanks! :))

Tutors, sign in to answer this question.

H(z) = ln [√(a^{2}-z^{2})/√(a^{2}+z^{2})]

= ln(a^{2}-z^{2})^{½ } - ln(a^{2}+z^{2})^{½}

= (½)ln(a^{2}-z^{2}) - (½)ln(a^{2}+z^{2})

H'(z) = -z/(a^{2}-z^{2}) -z/(a^{2}+z^{2})

= [-z(a^{2}+z^{2}) - z(a^{2}-z^{2})]/(a^{4}-z^{4}) = -2a^{2}z / (a^{4}-z^{4})

------------------------------------------------------------------------------

y = x^{lnx}

Use logarithmic differentiation to find y':

lny = ln(x^{lnx})

lny = (lnx)^{2}

y'/y = 2(lnx)/x

y' = y(2lnx/x) = x^{lnx}(2lnx/x) = 2lnx (x^{lnx - 1})

Thanks for your response.

I have a question, how did you get the derivative of (½)ln(a2-z2) - (½)ln(a2+z2)? I don't understand how you got H'(z) = -z/(a2-z2) -z/(a2+z2)

Thanks again! :))

Thanks again! :))

The derivative of y = ln(u) is u'/u

Assuming that a is a constant, the derivative of (1/2)ln(a^{2}+z^{2}) is

(1/2) [ 2z / (a^{2}+z^{2}) ] = z/(a^{2}+z^{2})

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments

H(z)= ln radical a^2-z^2/radical a^2+z^2 andfor the second one is y=x^lnx